Deducing the Impact of Physical Activity, Sedentary Behavior, and Physical Performance on Cognitive Function in Healthy Older Adults - Gerten, Sina; Engeroff, Tobias; Fleckenstein, Johannes; Füzéki, Eszter; Matura, Silke; Pilatus, Ulrich; Vogt, Lutz; Pantel, Johannes; Banzer, Winfried (Frontiers in Aging Neuroscience, 2022)
Objectives: Participating in physical activity and maintaining physical performance as well as reducing sedentary behavior are discussed to be beneficially associated with cognitive function in older adults. The purpose of this cross-sectional analysis was to differentiate the relevance of objectively measured physical activity, physical performance, and sedentary behavior on cognitive function in healthy older adults (n = 56, age = 76 ± 7 yrs, gender = 30 female). Methods: Accelerometer based physical activity and sedentary behavior were analyzed as minutes per week spent sedentary and physically active with light or moderate to vigorous intensity. Participants´ physical performance was assessed via cardiopulmonary exercise testing and analyzed as maximal workload and heart rate, heart rate reserve and peak oxygen uptake. The assessment of cognitive function included working memory, attention, executive function, and verbal memory. Data was analyzed with Spearman and partial correlations. Trial registration: NCT02343029. Results: Light physical activity was moderately associated with executive function (r = -.339, p = .015). Attention was significantly associated with maximal workload (r = -.286, p = .042) and peak oxygen uptake (r = -.337, p = .015). Working memory was associated with maximal workload (r = .329, p = .017). Conclusion: Whereas a broad range of cognitive function were beneficially linked to physical performance, light intensity activities in particular showed an impact on executive function. Our research underlines the need to separate the impact of maintained physical performance and current physical activity on cognitive function and highlights the relevance of light physical activity.